Analytical Study of Some Biokinematical Variables and Body Anthropometry and Their Relationship With Achievement In Basketball - Fares, Laith (Journal of Physical Education, 2012)
The research included the analysis of some biokinematical variables related to free throw skill in basketball to find the most important variables affecting the development of player and best achievement. The subjects of the research were (10) young league players of the season 201. All of these players were qualified for participating in west of Asia knock – out championships. The researcher used the descriptive research.The researcher came up with the following conclusions:1.the variable of ball entering the basket angle increased the player’s self – confidence (71)which scored the highest (biokinematical variable). 2.Highest of ball variable scored the lowest level in self – confidence.3.Overall length variable (71) which scored the highest in self confidence as body variable.4.The variable of ball entering the basket angle increased the player’s self – confidence (71) which scored the highest (biokinematical variable). 5. The length of torso variable achieved self confidence level (19) which is the lowest variable for body measurements.Finally the researcher recommended the following:1.Focusing on these variables during training.2.Studying other variables on the same subjects of this research.Making similar studies and researches for other variables related to sports events.